2016
DOI: 10.1002/2016jf003893
|View full text |Cite
|
Sign up to set email alerts
|

Changes in snow distribution and surface topography following a snowstorm on Antarctic sea ice

Abstract: Snow distribution over sea ice is an important control on sea ice physical and biological processes. We combine measurements of the atmospheric boundary layer and blowing snow on an Antarctic sea ice floe with terrestrial laser scanning to characterize a typical storm and its influence on the spatial patterns of snow distribution at resolutions of 1–10 cm over an area of 100 m × 100 m. The pre‐storm surface exhibits multidirectional elongated snow dunes formed behind aerodynamic obstacles. Newly deposited dune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
(76 reference statements)
1
22
0
Order By: Relevance
“…The spatial extension of these accumulation zones is generally lower than the extension of the erosion areas and the amount of deposited snow can locally reach 150 mm (liquid water equivalent) on the leeward sides of some crests. Similar contrasts between the extension of erosion and deposition zones have been reported by Trujillo et al () when studying snow redistribution on sea ice at high resolution (100 m × 100 m area).…”
Section: Resultsmentioning
confidence: 99%
“…The spatial extension of these accumulation zones is generally lower than the extension of the erosion areas and the amount of deposited snow can locally reach 150 mm (liquid water equivalent) on the leeward sides of some crests. Similar contrasts between the extension of erosion and deposition zones have been reported by Trujillo et al () when studying snow redistribution on sea ice at high resolution (100 m × 100 m area).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, for coarse‐resolution applications, subgrid snow‐depth spatial variability could be accounted for by combining the relative frequency information in Figure with the methods presented in Liston (), without actually simulating the distributions presented in Figures and . Trujillo et al () also suggested this approach may be valid at large scales. All of the components are in place to perform a wide variety of snow‐evolution simulations, ranging from local, to regional, to pan‐Arctic scales.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we focus on how snow, once deposited, is redistributed on the surface of sea ice: a topic whose importance in controlling the sea‐ice cover is increasingly clear. There are two key types of wind‐related snow‐accumulation features present on sea ice (Figure ; Iacozza & Barber, ; Lange & Eicken, ; Peters, ; Sturm et al, ; Sturm & Massom, ; Trujillo et al, ): (1) snowdrifts that form around ice pressure ridges and ice blocks that serve as topographic obstructions to the wind and (2) a relatively thin veneer snow that includes snow dunes and other bedforms on comparatively flat, undeformed ice. These two snow structures are analogous to snow erosion and deposition features found in terrestrial systems (e.g., Filhol & Sturm, ; Liston et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, ice-lenses or liquid water in snow heavily influence the microwave backscatter (Marshall et al, 2007), which is the basis for many satellite remote-sensing products. The problem of proper up-scaling snow properties is not peculiar to the complex terrain of mountains, but exists also for less complex topography such as Antarctic sea ice (Trujillo et al, 2016) or the Greenland ice sheet, where it is unknown how much melt water can be stored in snow and firn (Forster et al, 2014). 30…”
Section: Modeling Issues: Spatial Resolution and Physical Processes Imentioning
confidence: 99%